Identifying the gap and differences between customers' expectations for banks' corporate social responsibility and the actual scenario - Saeidi, Sayedeh Parastoo; Othman, Mohd Shahwahid; Streimikiene, Dalia; Saaeidi, Seyyed Alireza; Saeidi, Parvaneh; Mardani, Abbas (Kaunas Faculty of Humanities, Vilnius University, 2017)
The present study, for the first time, examines the gap between the customers' corporate social responsibility (CSR) expectations and the actual CSR engagement within the nonbranch banking industry. Therefore, the investigation identifies and compares the hierarchy of customers' CSR priorities relative to the bank managers' CSR priorities. In order to address the investigation, the present study fills the gaps of the literature by selecting the first formal and biggest non-branch bank in Iran, known as 'FaraBank', which is part of Mellat Bank (the second largest bank in Iran). The investigation is conducted in the form of a survey, with the data being gathered via questionnaires handed out to Farabank's managers and Mellat bank's customers. Several univariate statistics are implemented synthesize the answers relative to the research focused questions. The initial results revealed that the CSR implementation in Farabank is significantly higher than average weighted score of 4, and enabled the finding that customers have greater expectations compared to bank's actual CSR plan. However, among the five dimensions of CSR, the CSRs that addressed the responsibilities toward customers and community turned out as the top most priorities for both customers and managers in bank. Thereafter, the general CSR, employees, and finally shareholder dimensions are placed as the next priorities for customers, while, this is shareholders, employees, and at last general CSR for bank.